HUBUNGAN SIKAP DENGAN PEMENUHAN DIIT PADA KELUARGA BERISIKO DIABETES MELITUS DALAM MENCEGAH PENYAKIT DIABETES MELITUS TIPE 2 PADA MASA PANDEMI COVID-19 - Agustina Anggraini; Yesi Hasneli N; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Introduction: Diabetes mellitus (DM) is a metabolic disease that causes damage to the heart, blood vessels, and kidneys. DM can be passed down from parents to children. The ways to prevent DM is a balanced diet. The fulfillment of a person's diet is influenced by attitude factors. The purpose of this study to determine the relationship attitudes and diet fulfillment in families at risk of DM in preventing type 2 DM during covid-19 pandemic. Methods: This study used analytical observational design with a cross sectional approach. The research sample was 60 respondents using purposive sampling technique. The analysis used is univariate analysis and bivariate analysis using chi square test. Results: This study shows overview of respondents attitudes that 33 respondents (55%) have a negative attitude, 27 respondents (45%) have a positive attitude. Overview of the fulfillment of the respondents diet is that 32 respondents (53%) have a poor diet, 28 respondents (47%) have a good diet. Based on the chi square analysis, it was found that there a relationship between attitude and diet fulfillment in families at risk of type 2 DM with p value (0.000) < α (0.05). Conclusion: Attitude affects diet fulfillment in families at risk of Type 2 DM. Suggested to the health care is expected to provide information to the public about the importance of attitudes and diet fulfillment in preventing type 2 DM. Keywords: Attitudes; diet fulfillment; type 2 DM